Anatomic Study and Clinic Application of Transverse Circumflex Scapular Artery Perforator Flap Repair of Lower Limb Soft Tissue Defects in Children. (May 2020) - Pang, Xiaoyang; Cao, Zheming; Wu, Panfeng; Tang, Maolin; Qin, Liming; Yu, Fang; Zhou, Zhenbing; Tang, Juyu
Abstract : Purpose: The aim of this study was to demonstrate the viability of the transverse circumflex scapular artery perforator flap (TCSAPF) in children with soft tissue defects of the lower limb. Methods: In an anatomic study, 25 fresh cadavers were injected with lead oxide–gelatin for spiral computed tomography and 3-dimensional image reconstruction. In a 3-year clinical application study, children with soft tissue defects and exposed tendons and/or bones in the lower limb underwent free-TCSAPF repair of the defect. Results: Perforators from the transverse branch of the circumflex scapular artery were identified in both anatomical and clinical studies. The average external diameter was 0.9 ± 0.3 mm. Each perforator supplied an average area of 63.5 ± 16.8 cm 2 in anatomical. Twenty-one children were included in this group (9 boys, 12 girls, mean age, 6.6 ± 2.7 years). The size of the flaps ranged from 6 to 17 cm × 4.5 to 7 cm (average, 65.3 ± 22.6 cm 2 ). The average flap harvesting time was 30.1 ± 8.5 minutes, average operation time was 138.6 ± 31.5 minutes, and average blood loss was 89.5 ± 21.9 mL. The average length of the vessel pedicle was 8.2 ± 2.4 cm. Arterial congestion occurred in one child, 18 hours postoperatively; subsequent re-exploration and great saphenous vein transplantation were successful. Of the 3 children who had bulky flaps, 1 patient underwent defatting. Satisfactory outcomes included good appearance and function of the recipient and donor areas. Conclusions: The TCSAPF provides high-quality skin and vessel flexibility, providing a reliable blood supply in children. The flap has potential benefits over existing perforator flaps.